The first reported cases of meat allergy following tick bites in the UK. Issue 4 (April 2021) - Bansal, Rhea A; Bahal, Sameer; O'Brien, Rachael; Miller, Joanne; Bansal, Amolak S; Yong, Patrick FK
Allergic reactions frequently involve the production of immunoglobulin E (IgE) antibodies to proteins. However, reactions directed against carbohydrate moieties are increasingly being recognised. Tick bites can contribute to the development of immunoglobulin E to the galactose-1, 3-galactose (alpha-gal) moiety on tick salivary proteins. These IgE molecules can cross-react with alpha-gal found in red meats, causing Type I IgE-mediated hypersensitivity reactions to these foods. We present three cases of delayed reactions to beef, pork and lamb in patients with prior tick bites and in the presence of a positive-specific IgE to alpha-gal. Patients were advised to avoid red meat consumption and to carry emergency treatment in the form of anti-histamines with or without adrenaline autoinjector devices. This is the first published report of red meat allergy caused by tick bites suffered in the UK.